2018
DOI: 10.3389/fped.2018.00040
|View full text |Cite
|
Sign up to set email alerts
|

Training Effects of the FIFA 11+ Kids on Physical Performance in Youth Football Players: A Randomized Control Trial

Abstract: ObjectiveTo analyze the training effects of the FIFA 11+ kids on several parameters of physical performance in male youth football players.Materials and methodsTwenty-three youth players were randomized within each team into two groups (control vs. intervention). The intervention group performed the FIFA 11+ kids programme 2 times a week for 4 weeks; the control groups completed their normal warm-up routines. Thirteen physical performance measures {range of motion (hip, knee, and ankle joints), dynamic postura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 36 publications
6
72
1
3
Order By: Relevance
“…Significant differences were found in favor of FIFA 11+group, but 1 month after the treatment when they stopped applying the program, the vertical jump results were back at the level of the initial measurement, which led to the conclusion that the program should be further applied since the program did not show the presence of long-term effects. Pomares-Noguera et al showed that only 4 weeks of the application of the FIFA 11+ kids program is enough to provide better physical performance in relation to the standard method of warming up in youth football players [15]. This was confirmed in the present study where FIFA 11+ elicited significant improvement for standing long jump (5.6%; p = 0.001).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Significant differences were found in favor of FIFA 11+group, but 1 month after the treatment when they stopped applying the program, the vertical jump results were back at the level of the initial measurement, which led to the conclusion that the program should be further applied since the program did not show the presence of long-term effects. Pomares-Noguera et al showed that only 4 weeks of the application of the FIFA 11+ kids program is enough to provide better physical performance in relation to the standard method of warming up in youth football players [15]. This was confirmed in the present study where FIFA 11+ elicited significant improvement for standing long jump (5.6%; p = 0.001).…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, our results showed small (1.9%) but significant improvement (p = 0.046) for Illinois agility test after only 4 weeks of the FIFA 11+ program [7]. Similar improvements after 4 weeks also have been reported in agility run after the implementation of FIFA 11+ kids in a large cohort of football players the same age as in our study [15].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations